[Black Beach at Eldfell] - Streng, Evelyn Fiedler (1975)
Photograph of a black beach near Eldfell. The dark beach sits along the turquoise ocean, an orange, rock platform is visible along the left edge of the photograph. Another tall island made of brown rock and covered in grass is visible in the distance to the left.